Canada : 2009 Article IV Consultation; Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2009)
The staff report on Canada's 2009 Article IV Consultation examines economic developments and policies. Canadian banks have weathered the crisis better than major-country peers, but the credit cycle will be challenging, particularly given high household debt. Financial instability is a tail risk, but heightened vigilance is warranted. The Bank of Canada has appropriately loosened monetary policy, bringing the policy rate target to a record-low 1\2 percent. Macroeconomic policies have adopted an expansionary tilt, and authorities have taken steps to safeguard financial stability.